2022
DOI: 10.4314/bcse.v35i3.19
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents and acetylcholinesterase inhibitory activity of Beilschmiedia insignis Gamble

Abstract: ABSTRACT. Secondary metabolites from natural products are potential sources of acetylcholinesterase inhibitors, which are key enzymes in the treatment of many neurodegenerative diseases. Inspired by the reported activities of alkaloids herein we report the chemical investigation on the chemical constituents from Beilschmiedia insignis and their acetylcholinesterase inhibitory activity. Isolation of the stem bark of B. insignis led to the isolation and identification of five aporphine alkaloids, namely isocoryd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Investigation of the chemical constituents from the leaves of D. argentea has led to the isolation of eight compounds. These metabolites were identified by analysing their spectroscopic data and comparing it with the literature data (Salleh et al, 2021a;Salleh et al, 2021b;Salleh et al, 2021c;Shakri et al, 2021;Romes et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Investigation of the chemical constituents from the leaves of D. argentea has led to the isolation of eight compounds. These metabolites were identified by analysing their spectroscopic data and comparing it with the literature data (Salleh et al, 2021a;Salleh et al, 2021b;Salleh et al, 2021c;Shakri et al, 2021;Romes et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Owing to its several bioactive compounds proven to have anti-Alzheimer activities (mediating Aβ-toxicity, inhibiting related targets e.g. acetylcholinesterase), such as sitosterol [ 21 , [27] , [28] , [29] ]. Recent research has also shown that KL peel extract exhibits a neuroprotective effect against oxidative stress [ 64 ] and improves spatial memory [ 65 ] in mice in vivo studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, bioactive compounds of KL, such as sitosterol, are known to exhibit anti-AD properties. Sitoserol is reported to be a good inhibitor of cholinesterase (AChE), capable of preventing glutamate and Aβ toxicity, and possesses antioxidant activity [ 21 , [27] , [28] , [29] ].…”
Section: Introductionmentioning
confidence: 99%
“…Natural medicinal plants are rapidly being recognized as a rich source of bioactive chemicals with therapeutic potential. Among these, the genus Beilschmiedia, which contains about 250 species and is common in Africa and Asia, has attracted interest due to its various chemical compositions and therapeutic capabilities (Salleh et al, 2016a(Salleh et al, , 2019(Salleh et al, , 2020(Salleh et al, , and 2021. Beilschmiedia pulverulenta, also known as 'medang merah' in Malaysia and found in Peninsular Malaysia, Borneo, and Indonesia, is one such species that thrives in mixed dipterocarp forests on sandy loam soils (Salleh et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%